Residual Cultural Imperialism in Primary Textbooks in Bangladesh: A Critique of the English for Today Textbooks - Jahan, Ms. Akhter (EAST WEST JOURNAL OF HUMANITIES, 2012)
It has been assumed that with the rising importance of English as a global language (Crystal, 1997) that ’the centre’ (native English speaking countries) produced ELT materials have become tools, using which linguistic as well as cultural imperialism may take place in ’the periphery’ (non-native English speaking countries) contexts marginalizing local needs and cultures (Phillipson 1992; Pennycook, 1994; Kumaravadivelu, 2003, 2006). Therefore, the authorial ownership of materials can be given to local experts who know about the culture, needs and realities of local communities (Kumaravadivelu, 2006). Taking these issues into account, this paper aims to examine how far the locally produced textbooks, English for Today (Class 1-5), have been able to resist cultural imperialism at the primary level in Bangladesh. The analysis of the cultural contents of these textbooks reveals that though these locally produced materials have been able to resist cultural imperialism to some extent, they still have some limitations regarding the way exposure has been provided to the local as well as the target cultures.